Regional Differentiation of the Constituent Entities of the Russian Federation by the Level of Socio-Economic Development - Sadovnikova, Natalia A; Davletshina, Leysan A; Zolotareva, Olga A; Lebedinskaya, Olga O (Edelweiss Applied Science and Technology, 2021)
This article presents the results of a cluster analysis of the regions of the Russian Federation in terms of the main parameters of socio-economic. The major objective of the article is to develop a method for the division of the Russian regions into clusters in order to improve the quality of the policymaking process. The authors studied and analyzed the domestic and foreign (Eurostat) methodology for assessing the socio-economic development of territories. The major results of the study are the determination of the main parameters of territorial differentiation and identification of the key indicators that affect the socio-economic development of Russian regions. The authors have carried out a classification of the constituent entities of the Russian Federation not in terms of territorial location and geographical features, but in terms of the specifics and key parameters of the socio-economic situation into 4 clusters. The results of the cluster analysis allow specifying specific areas, where state control and interference is needed in order to ease the economic and social inequity in Russia and cease social unrest.